QUICK ATTACK AND DEFENSE TACTICS IN FOOTBALL PLAYERS - Uraimov Sanjar Rozmatovich; Eshimov Temur (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
Football game during surface of upcoming tactical tasks most of them combinations by means of solution will be done . Combination is a specific tactical task solution doing two or one how many player i ng actions is the whole game combinations and to him against actions from the chain consists of Combinations in this in advance trainings in time prepared placed and prepared not put , that is of the game himself during surface .